Integrating the Unstructured: Ridehailing as a Catalyst in Jakarta’s Multimodal Transport System - Zulkarnain, Ahnis; Prasojo, Genny Luhung; Nashrullah (Indonesian Scientific Publication, 2025)
Jakarta’s public transport system has undergone rapid expansion and integration, aiming to improve accessibility and user experience through initiatives like Jak Lingko. Despite these efforts, first and last mile challenges remain, increasingly addressed by ridehailing services such as Gojek and Grab. This study investigates the extent to which ridehailing supports Jakarta’s multimodal public transport network. A qualitative descriptive approach was employed, using secondary data from BPS Jakarta, Kompas Research 2025, Wikipedia, and the Asian Transport Observatory. The analysis focused on ridehailing usage, ridership trends across MRT, LRT, KRL, and Transjakarta, and Jak Lingko’s fare integration structure. Results reveal that 71.7% of public transport users rely on ridehailing, with 75% using it for first/last mile access. Ridership remains high: Transjakarta ( 1M daily), KRL ( 984K weekday), MRT ( 111K), and LRT ( 70K). Integration via Jak Lingko simplifies fare payment but gaps persist in physical connectivity and equity. The study concludes that ridehailing is essential in Jakarta’s transport landscape. Formalizing its role through adaptive policy, public private cooperation, and inclusive governance can ensure more sustainable and accessible urban mobility.